The Formation of the Basics of Social Insurance During the 17th – 19th Centuries - Bodnaruk, Mykola (the Journal of Eastern European Law, 2017)
The issue of social protection of the population and providing it with social assistance, combined with the introduction of social insurance, is very capacious and prolific. However, in spite of its broad scope, we should admit considerable social significance of the field of social insurance and providing necessary social assistance to the population. After all, the “indicators” of this system’s prosperity and flexibility enable us to make certain judgments concerning the level of the country’s social-economic well-being, concerning the functioning of the respective social institutions, concerning the level of society’s openness, and, finally, concerning the ability to maintain the interaction between the authorities and the society. The degree of well-being of the unprotected layers of society lets us judge about the level of its development. History is full of cases, when society performed the functions of the state in the field of providing social assistance to the population, establishing different mutual assistance funds, collecting donations, etc. The above phenomenon also finds its way in the modern life of our country, when volunteers help not only the Ukrainian Armed Forces (the latter opposing to Russian aggression in the east of the country), but also the population of the areas, where the military conflict takes place. This fact is unique and requires further scientific investigation. It is worth mentioning that Ukrainian state does not neglect its citizens living in the conflict zone, but keeps paying them out pensions, social allowances, etc. We suppose, it proves that both Ukrainian society and the Ukrainian state possess an adequate level of development, being able to provide the respective state institutions of our country. As the proverb says: “Nothing can arise of nothing”. Therefore, we had a goal of thorough researching the processes that took place on the territory of Ukraine in the XVII-XIX centuries. The processes that have caused the formation and development of social assistance for the population, as well as its normative-regulatory backing due to the system of social insurance of the Ukrainian population.
Keywords: взаємодопомога; соціальне страхування; право соціального забезпечення; страхування,; історія права; взаимопомощь; социальное страхование; право социального обеспечения; страхование; история права; mutual help; social insurance; Social Security Law; insurance; History of Law